2022
DOI: 10.3390/nu14081611
|View full text |Cite
|
Sign up to set email alerts
|

Actions of Retinoic Acid in the Pathophysiology of HIV Infection

Abstract: The vitamin A metabolite all-trans retinoic acid (RA) plays a key role in tissue homeostasis and mucosal immunity. RA is produced by gut-associated dendritic cells, which are among the first cells encountered by HIV. Acute HIV infection results in rapid reduction of RA levels and dysregulation of immune cell populations whose identities and function are largely controlled by RA. Here, we discuss the potential link between the roles played by RA in shaping intestinal immune responses and the manifestations and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 101 publications
1
8
0
Order By: Relevance
“…To test this hypothesis, biologically relevant retinoids were quantified in the RM plasma across several time points, including baseline (prior to CD8 depletion and infection), day 14 (acute infection), day 98 (therapy), and day 161 (63 days post-cART interruption) ( Figure 4(a) ). Consistent with results from previous studies, acute infection was associated with a significant decrease in plasma atRA levels in both control and anti-α4β7-treated groups [ 22 , 40 ]. Plasma atRA levels remained depressed in the control animals during subsequent sampling.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…To test this hypothesis, biologically relevant retinoids were quantified in the RM plasma across several time points, including baseline (prior to CD8 depletion and infection), day 14 (acute infection), day 98 (therapy), and day 161 (63 days post-cART interruption) ( Figure 4(a) ). Consistent with results from previous studies, acute infection was associated with a significant decrease in plasma atRA levels in both control and anti-α4β7-treated groups [ 22 , 40 ]. Plasma atRA levels remained depressed in the control animals during subsequent sampling.…”
Section: Resultssupporting
confidence: 91%
“…atRA plays a pleiotropic role in the gut mucosa. Produced by both the intestinal epithelium and CD103+ dendritic cells (DCs), its generation and release signals for a significant immunomodulatory response, including the differentiation of pro-tolerogenic T-reg cells, IgA class-switching, and regulation of lymphocyte effector function [ 22 ]. Additionally, atRA induces the expression of both CCR9 and the aforementioned α4β7 integrin on diverse immune cell subsets [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the course of these studies we determined that, in the presence of RA, signaling by both HIV gp120 and MAdCAM-1 activates cells in a way that supports HIV infection [ 1 , 9 , 11 ]. Both RA and MAdCAM-1 are modulated in the context of HIV and SIV infection [ 72 , 73 ]. These observations raise the question as to how signaling through α 4 β 7 impacts CD4 + T cell differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…The plasma retinoid assays showed that HIV infection did not affect the generation of RA substrates (retinol) or stored retinoids, indicating that RA decreases were driven by a metabolic malfunction 9 . According to preliminary in vitro investigations done using human CD4+ T-cell line, HIV infection was found to lower RA production, although plasma RA levels in HIV-infected patients were similar to those of NHP 9,10 . HIV-1 transgenic mice (Tg26) glomeruli also found to have poor RA metabolism 11 .…”
Section: Introductionmentioning
confidence: 96%
“…HIV-infected people are reported to have decreased plasma RA levels 8,9 . In an NHP (nonhuman primate) HIV model, plasma Retinoic Acid dropped, indicating acute VitA deficiency (VAD).…”
Section: Introductionmentioning
confidence: 99%